Potential of Pumpkin Flour as a Stabilizer in Reduced-Fat Mayonnaise (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
Pumpkin is a local plant that contains antioxidants such as polyphenols and carotenoids. Pumpkin contains pectin which can function as a stabilizer. Â Full-fat mayonnaise is a semi-solid emulsion product that has a total fat content of 70-80%, while reduced-fat mayonnaise has a fat content of 50-60%. Pumpkin flour can be applied to reduced-fat mayonnaise in terms of physicochemical quality. This research was conducted using a laboratory experimental method and a completely randomized design. The physicochemical qualities of reduced-fat mayonnaise include fiber content, fat content, viscosity, and antioxidant activity. The results of added pumpkin flour have a highly significant effect (P<0.01) on fiber content, fat content, viscosity, and antioxidant activity. The physicochemical qualities of reduced-fat mayonnaise with pumpkin flour are as follows 0.90% fiber content, 50.57% fat content, 4443 cP viscosity, and 21.03% antioxidant activity, respectively. Â It can be conclude that the use of 6% yellow pumpkin flour was the best treatment for reduced-fat mayonnaise. The most types of fatty acids in the best treatment were palmitic, oleic, and linoleic acids.